Respuesta :

Hello.

For the first one its 
x = -0.2 + -0.4y

Move all terms containing x to the left, all other terms to the right.

  Add '-2y' to each side of the equation

. 5x + 2y + -2y = -1 + -2y Combine like terms: 2y + -2y = 0 5x + 0 = -1 + -2y 5x = -1 + -2y

 Divide each side by '5'. x = -0.2 + -0.4y

For the second its 
x=−y+2


Step 1: Flip the equation.−x+2=y


Step 2: Add -2 to both sides.−x+2+−2=y+−2−x=y−2


Step 3: Divide both sides by -1.−x−1=y−2−1x=−y+2

Have a nice day

ACCESS MORE